2013
DOI: 10.1038/npp.2013.195
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in White Matter Microstructure Associated with Chronic Ketamine Use

Abstract: Ketamine is an N-methyl-D-aspartate (NMDA) receptor antagonist that has been found to induce schizophrenia-type symptoms in humans and is a potent and fast-acting antidepressant. It is also a relatively widespread drug of abuse, particularly in China and the UK. Acute administration has been well characterized, but the effect of extended periods of ketamine use-on brain structure in humansremains poorly understood. We measured indices of white matter microstructural integrity and connectivity in the brain of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 49 publications
2
20
1
Order By: Relevance
“…A previous study reported that ketamine was associated with impairment of working, episodic, and procedural memory function,43 and long-term ketamine abuse could result in persistent neurocognitive impairments44 and even potential harmful brain changes 45. Although our study indicated that ketamine might have rapid antidepressant effects in patients with TRD, its impact on the neurocognitive function of patients with TRD has been assessed by only few studies to date.…”
Section: Discussionmentioning
confidence: 56%
“…A previous study reported that ketamine was associated with impairment of working, episodic, and procedural memory function,43 and long-term ketamine abuse could result in persistent neurocognitive impairments44 and even potential harmful brain changes 45. Although our study indicated that ketamine might have rapid antidepressant effects in patients with TRD, its impact on the neurocognitive function of patients with TRD has been assessed by only few studies to date.…”
Section: Discussionmentioning
confidence: 56%
“…Although this suggests that impaired connectivity can be rescued, it is critical to understand ketamine’s impact on white matter. Efforts should be aimed at distinguishing between acute and chronic effects, as chronic ketamine usage has been shown to disrupt connectivity between the caudate and PFC 103. Focusing attention on understanding the molecular substrates that influence white-matter integrity would be an important research avenue.…”
Section: Connectomicsmentioning
confidence: 99%
“…With regard to the FP pathway, a recent study suggests that psychotic patients have glutamate-related dysregulation of the brain network supporting cognitive control (Falkenberg et al, 2014 ). The NMDAR antagonist ketamine induces psychotic-like experiences that are highly reminiscent of those observed in schizophrenia (Krystal et al, 1994 , 2005 ; Schmidt et al, 2012 ), so it is intriguing that this also reduces diffusivity in the superior longitudinal fasciculus (Edward Roberts et al, 2014 ). It has further been demonstrated that ketamine reduced the negative correlation between the FP system and the default network in healthy volunteers, while the degree of this disruption predicted task performance (Anticevic et al, 2012 ).…”
Section: Nmdar Function and Fp Dysconnectivity In Psychosismentioning
confidence: 99%